HIV voluntary counseling and testing and HIV incidence in male injecting drug users in northern Thailand: Evidence of an urgent need for HIV prevention - Surinda Kawichai (2018)
HIV voluntary counseling and testing (VCT), an important strategy for HIV prevention and care, has been available in all government hospitals in Thailand since 1992. We assessed factors associated with HIV testing, its uptake, and estimates of HIV incidence after HIV testing among male northern Thai injecting drug users (IDUs) admitted for inpatient drug treatment. Participants were interviewed about risk behaviors and HIV testing history before VCT was provided as part of the study. Of 825 IDUs who participated, 36% reported a prior HIV test. Factors associated with prior HIV testing in multiple logistic regression analysis included higher education and having >1 lifetime sex partner. Needle sharing was not associated with prior HIV testing. Of the 298 men with a prior test, 80% reported a negative result on their last prior HIV test, of whom 28% tested positive in our study, leading to an estimated incidence rate of 10.2 per 100 person-years. Fifty-nine percent of the IDUs who reported a prior HIV test stated that they did not receive pre- and/or posttest counseling. HIV incidence among IDUs remains high despite having VCT. Extending HIV prevention and harm reduction programs is urgently needed for IDUs in the region. Copyright © 2006 by Lippincott Williams & Wilkins.